CIRCADIAN BLOOD PRESSURE PATTERNS IN TYPE 2 DIABETIC PATIENTS WITH CARDIOVASCULAR FORM OF DIABETIC AUTONOMIC NEUROPATHY (Global Conference on Medical and Health Sciences, 2026)
To analyze the 24-hour blood pressure profile in patients with type 2 diabetes mellitus (T2DM) with the cardiovascular form of diabetic autonomic neuropathy (CAN).Materials and methods: Based on the time-domain and frequency-domain analysis of 24-hour Holter ECG monitoring, the patients were divided into two groups. Group 1 included patients without this complication — CAN (−). Group 2 consisted of patients with CAN (+). Group 1 comprised 62 patients with a mean age of 54.9 ± 0.69 years and a mean disease duration of 7.54 ± 0.28 years (39 women and 23 men). Group 2 included 84 patients with T2DM, mean age 56.3 ± 0.61 years, mean disease duration 7.5 ± 2.6 years (52 women and 32 men). None of the included patients were taking antihypertensive medications.